Length-weight relationship, size structure, and conservation implications of endangered humphead wrasse (Cheilinus undulatus) in the Banggai Archipelago, Indonesia - YEHIEL H. DASMASELA; DIETRIECH G. BENGEN; I WAYAN NURJAYA; FRENSLY D. HUKOM (Society for Indonesian Biodiversity, 2026)
Abstract. Dasmasela YH, Bengen DG, Nurjaya IW, Hukom FD. 2026. Length-weight relationship, size structure, and conservation implications of endangered humphead wrasse (Cheilinus undulatus) in the Banggai Archipelago, Indonesia. Biodiversitas 27 (7): d270714. https://doi.org/10.13057/biodiv/d270714. The humphead wrasse (Cheilinus undulatus) is an endangered coral reef fish that has experienced substantial population declines associated with overexploitation in the live reef fish trade. This study integrates analyses of the length-weight relationship (LWR), size structure, condition factor, and morphology-based sex-phase classification to provide baseline biological information for conservation planning and fisheries management. Sampling was conducted from June to September 2022 using a fishery-dependent approach linked to local live reef fish trade networks. A total of 163 specimens were measured for total length and body weight, ranging from 150 to 590 mm and 100 to 3,500 g, respectively, with most specimens concentrated within the 249.5-449.5 mm size classes. The LWR followed the equation W: 0.00490L3.33, indicating positive allometric growth (b: 3.33) with a strong model fit (R2: 0.878). Approximately 98% of the sampled fish belonged to small-to-medium-sized juvenile and female-phase categories, whereas no morphologically identifiable adult males were recorded. This size structure indicates demographic truncation, with potential implications for reproductive resilience under continued exploitation pressure. Sex-phase classification was inferred from external morphology without gonadal validation. The mean condition factor (K: 1.56) indicated generally good physiological condition. Nevertheless, the sampled population was dominated by smaller individuals, whereas large-bodied fish and adult males were poorly represented. This contrast highlights that individual physiological conditions and demographic structures may reflect different aspects of population status rather than the same underlying process. Large individuals were uncommon in the sampled population, a pattern consistent with observations from other exploited populations of this protogynous species. These findings provide baseline biological information to support integrated management approaches combining size-based regulation, habitat protection, and long-term population monitoring for the conservation of C. undulatus from the Banggai Archipelago.